Modeling of fracture toughness of composite materials - Goldstein, Robert Veniaminovich; Perelmuter, Mikhail Natanovich (Computational Continuum Mechanics, 2009)
A model of fracture of composites materials and adhesion junctions is proposed. The model is based on the analysis of the process zone formed near the crack tip. It is assumed that the process zone is a layer of finite length with weakened bonds between the material particles (the end zone). This zone is considered as a part of the crack. The interaction of crack surfaces is modeled by applying adhesion forces caused by bonds to crack surfaces. In the framework of the present end-zone model, the analysis of the limit equilibrium of cracks involves: (a) definition of relationships between adhesion forces and crack opening, (b) evaluation of displacements and stresses around the crack taking account of external loads and adhesion forces, and (c) definition of the dependence of critical external loads on the crack length. The analysis is based on a fracture criterion with an energy conditionfor the advance of the crack tipand a kinematic condition of the bond rupture. The results of calculation of fracture parameters are presented.